Urban waterfront protection: retrofitting the Briarcliff Waterfront District using systematic approaches with blue-green infrastructure - Brizendine, Noah (Kansas State University, 2023)
Blue-Green Infrastructure (BGI) has become an increasingly important best management practice (BMP) when it comes to stormwater runoff and flooding. Most modern-day engineering-based stormwater management strategies, often referred to as grey infrastructure, are made of impervious material leading to increases in flooding and water contamination. One of the main goals of BGI is to reduce impervious surfaces and focus on more natural systems using vegetation. BGI typologies perform differently in different site conditions, and therefore it is important to study these components to determine their flood management performance. This project systematically studies BGI typologies using a site suitability matrix and precedent analysis framework to determine the performance of each typology. Water management selection criteria based off current site conditions (drainage, soil type, topography, etc.) were used to demonstrate performance of each BGI typology. Precedent analyses helped assess the BGI typologies by providing real-world examples of their performance and usage as design features. The information collected contributes to a site analysis process influencing design decisions that can be adapted to guide BGI design near and within communities that are vulnerable to flooding.
Keywords: Blue-green; Infrastructure; Flooding; Briarcliff; Low-impact development